KOMUNIKASI PEMERINTAHAN YANG TEPAT DIGUNAKAN DALAM MASYARAKAT PEDESAAN - Rayinda E.42008073 (FISIP Universitas Tanjungpura Pontianak, 2012)
This thesis writing is intended to identify and to describe the communication process that hasimplemented by the Government of Pal IX Village in implementing the making of ElectronicIdentity Card (e-KTP) in Pal IX Village. The title of this thesis raised based on the support and theparticipation issue of the people of Pal IX Village which is not optimal yet in implementing themaking of e-KTP. This research uses descriptive method with qualitative paradigm. This researchwhich concerns about the communication process is measured by using the components of thecommunication achievement according to Harrold Laswell. Those components are communicator,content of message, communication channel, communicant, and feedback. The result of thisresearch showed that there is a relation between the communication of the governance of Pal IXVillage and the implementation of the making of e-KTP in the office of Sungai Kakap District. Italso means that the communication process that implemented by the Government of Pal IX Villagein informing the e-KTP program to the people has an effect to optimize the implementation of themaking of e-KTP.Keywords : Communication, Electronic Identity Card (e-KTP).